Blockade of TRPC Channels Limits Cholinergic-Driven Hyperexcitability and Seizure Susceptibility After Traumatic Brain Injury - Carver, Chase M.; DeWitt, Haley R.; Stoja, Aiola P.; Shapiro, Mark S. (Frontiers in Neuroscience, 2021)
We investigated the contribution of excitatory TRPC cation channels to post-traumatic hyperexcitability in the brain 7 days following controlled cortical impact model of traumatic brain injury (TBI) to the parietal cortex in male adult mice. We hypothesized that TRPC 1/4/5 channels are upregulated in excitatory neurons after TBI in contribution to epileptogenic hyperexcitability in key hippocampal and cortical circuits with substantial cholinergic innervation. This was tested by measuring TRPC1/4/5 protein and mRNA expression, assays of cholinergic function, neuronal Ca2+ imaging in brain slices, and seizure susceptibility after TBI. We found region-specific increases in expression of TRPC1, 4, & 5 subunits in hippocampus and cortex following TBI. The dentate gyrus, CA3 region, and cortex each exhibited robust upregulation of TRPC4 mRNA and protein. TBI increased cFos activity in dentate gyrus granule cells (DGGCs) and layer 5 pyramidal neurons both during TBI and 7 days post-TBI. DGGCs displayed greater magnitude and duration of ACh-induced rises in intracellular Ca2+ in brain slices from mice subjected to TBI. The TBI mice also exhibited greater seizure susceptibility in response to pentylenetetrazol-induced kindling. Blockade of TRPC4/5 channels with M084 reduced neuronal hyperexcitation and impeded epileptogenic progression of kindling. We observed that the time-dependent upregulation of TRPC4/5-containing channels alters cholinergic responses and activity of principal neurons that increase pro-excitatory sensitivity. The underlying mechanism includes acutely decreased acetylcholinesterase function, resulting in greater Gq/11-coupled muscarinic receptor activation of TRPC channels. Overall, our evidence suggests that TBI-induced plasticity of TRPC channels strongly contributes to overt hyperexcitability and primes the hippocampus and cortex for seizures.